Concurrent Chronic Exertional Compartment Syndrome and Popliteal Artery Entrapment Syndrome - Tiffany R. Bellomo; Connie Hsu; Pavan Bolla; Abhisekh Mohapatra; Dana Helice Kotler (Diagnostics, 2024)
Exertional leg pain occurs with notable frequency among athletes and poses diagnostic challenges to clinicians due to overlapping symptomatology. In this case report, we delineate the clinical presentation of a young collegiate soccer player who endured two years of progressive bilateral exertional calf pain and ankle weakness during athletic activity. The initial assessment yielded a diagnosis of chronic exertional compartment syndrome (CECS), predicated on the results of compartment testing. However, her clinical presentation was suspicious for concurrent type VI popliteal artery entrapment syndrome (PAES), prompting further radiographic testing of magnetic resonance angiography (MRA). MRA revealed severe arterial spasm with plantarflexion bilaterally, corroborating the additional diagnosis of PEAS. Given the worsening symptoms, the patient underwent open popliteal entrapment release of the right leg. Although CECS and PAES are both known phenomena that are observed in collegiate athletes, their co-occurrence is uncommon owing to their different pathophysiological underpinnings. This case underscores the importance for clinicians to be aware that the successful diagnosis of one condition does not exclude the possibility of a secondary, unrelated pathology. This case also highlights the importance of dynamic imaging modalities, including point-of-care ultrasound, dynamic MRA, and dynamic angiogram.